Bodies of desire: use of nonprescribed hormones among transgender women and travestis in five Brazilian capitals (2019-2021) - Katia Cristina Bassichetto; Thiago Félix Pinheiro; Claudia Barros; Paula Andrea Morelli Fonseca; Rita Suely Bacuri de Queiroz; Sandro Sperandei; Maria Amélia de Sousa Mascena Veras (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2024)
ABSTRACT Objective: To analyze the experiences of transgender women and travestis regarding the use of hormones for body changes without a medical prescription. Methods: This is a cross-sectional, quantitative and qualitative study, using data from "TransOdara", which estimated the prevalence of Sexually Transmitted Infections in transgender women and travestis recruited through Respondent-Driven Sampling, between December 2019 and July 2021, in São Paulo, Campo Grande, Manaus, Porto Alegre, and Salvador, Brazil. The main outcome was: use of hormones without medical prescription and associated risk factors. Descriptive analysis, mixed univariate logistic regression models, and semi-structured interviews were carried out. Results: Of the 1,317 recruited participants, 85.9% had already used hormones. The current use of hormones was reported by 40.7% (536) of them. Of those who were able to inform the place where they obtained them, 72.6% (381/525) used them without a medical prescription. The variables associated with the outcome were: current full-time sex work (OR 4.59; 95%CI 1.90-11.06) or in the past (OR 1.92; 95%CI 1.10-3.34), not having changed their name (OR 3.59; 95%CI 2.23-5.76), not currently studying (OR 1.83; 95%CI 1.07-3.13), being younger (OR 2.16; 95%CI 1.31-3.56), and having suffered discrimination at some point in life for being a transgender women and travestis (OR 0.40; 95%CI 0.20-0.81). Conclusion: The use of nonprescribed hormones is high among transgender women and travestis, especially among those who are younger, did not study, have not changed their name, and with a history of sex work. This use is related to the urgency for gender transition, with excessive use and damage to health.